Study on wireless power transfer based on magnetic resonance using inductive coil - Syaiful Anas Ibrahim (School of Electrical Systems Engineering, University Malaysia Perlis, 2015)
In this research, the inductance expression based on Current Sheet Approximation and Modified Wheeler Formula are proposed. Simulations show that the change of the number of turns and air gap distance are found to be affecting the power transfer efficiency. Simulation results showed that the model of WPT system achieved the highest efficiency 99.5% at a distance of 30 cm and resonant frequency of 12.05 MHz.